Reaching the Unreached - Through SHG Bank Linkage - Bhalla, Pooja; Kaur, Gagandeep (Indian Journal of Finance, 2008)
Halving global poverty is one of the most important Millennium Development Goals (MDGs) as set out at the Millennium Summit in New York in Sept. 2000. Almost all the countries in the world including India have committed themselves to attaining the MDGs by the year 2015. India is the second most populous country having more than one billion population. Over 22% of its population is living below poverty line. Increasing access to credit has always remained at the core of government’s planning in its fight against poverty. The GOI, since independence has been making concerted efforts in this direction viz., nationalization of existing private commercial banks, massive expansion of branch network in rural areas, mandatory directed credit to priority sectors of the economy, subsidized rates of interest and creation of a new set of rural banks at district level and an apex bank for agriculture and rural development (NABARD) at national level. But the institutional structure was neither profitable in rural lending nor serving the needs of the poorest. In short, it had created a structure "quantitatively impressive but qualitatively week"(Misra, Alok, Sept. 18, 2006) The failure of financial institutions to deal with poor borrowers in an imaginative and sustainable way and the inaccessibility of these institutions to the poor is stated to be the major disadvantages of the existing system (Swaminathan, Madhura 2007). Micro credit institutions are seen as being able to rectify these weaknesses. Microfinance is the new mantra in rural finance. It has been recognized world over as an effective tool for poverty alleviation and improving socio-economic status of rural poor. Micro finance refers to the programs that provide credit or self-employment and other financial and business service, including savings and technical assistance to the poor persons (Micro Credit Summit held in US in February1997). Micro finance services are available at the doorstep of the poorest at affordable price and the institution that provides service does not give it as a charity, but as a business proposition. Sums involved are small, but the coverage is vast, which means number-wise a huge chunk of the population is covered.